PENERAPAN APLIKASI ACCURATE DALAM PENYUSUNAN LAPORAN KEUANGAN PADA UMKM KERIPIK TEMPE SANAH - Caecilia Rosma Widyohening (Politeknik Sawunggalih Aji, 2023)
Micro, Small, and Medium Enterprises of Tempe Chips Sanah is one of the manufacturing companies engaged in industry or manufacturing that produces tempe chips. Accounting records for Micro, Small, and Medium Enterprises Sanah Tempe Chips are still very simple and manual, namely recording cash in, cash out, and accounts receivable. Micro, Small, and Medium Enterprises Sanah Tempe Chips have not made a distinction on assets, this is due to a lack of knowledge about how to prepare financial statements. This results in the company's financial information being inaccurate. The research method in this study uses quantitative data, namely about the average number of production per month, the selling price of the product, and the salaries of employees. Researchers compiled financial reports for Micro, Small, and Medium Enterprises with Tempe Sanah Chips using the Accurate Accounting version 4 application. Accurate Accounting version 4 is accounting software that has provided accounts that can be adapted to the type of company, making it easier to prepare financial reports. The reports produced are statements of financial position, income statements, and notes to financial statements as of January 31, 2021 in accordance with accounting principles based on Financial Accounting Standards for Micro, Small, and Medium Entities. The results of this final report are financial reports on the Tempe Sanah Chips MSME using the Accurate Accounting version 4. Financial report is made to find out information about the statement of financial position, profit report so that it can be used as a means of making decisions in the future. While the application is used so that the process of preparing reports is faster and more accurate.